Penyalahgunaan Narkoba Di Kabupaten Pohuwato Ditinjau Dari Periskop Kriminologi - Ni Wayan Erlianti; Lisnawaty W. Badu; Jufryanto Puluhulawa (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
The research discusses the factors causing drug abuse cases and their countermeasures in Pohuwato Regency. The method used in the research is empirical with qualitative descriptive data analysis that describes and describes reality data in the field. Based on the results of the study, that the factors that cause drug abuse cases in Pohuwato Regency are internally derived from within a person. Where the inability to adjust and weak self-confidence so that the perpetrator is unable to control the desire to try and have experience with drugs that are expected to overcome the mental pressure he experiences. The pressure in question comes from family circumstances that are less supportive (not harmonious) and indifferent to one's self-development. In addition, there are external factors, namely the promiscuity of the perpetrator, social and work environment factors, economic problems and easy access for the perpetrator. Police Countermeasures against Drug Crimes in Pohuwato Regency are carried out by conducting Early Prevention or Pre-emtif efforts by conducting searches regarding the causes or drivers, to the opportunities for the use of these illegal drugs. Early prevention is carried out through education that aims to create awareness and vigilance, by distributing banners and advertising banners and invitations not to use drugs in agencies and public service places including in the school environment. Preventive efforts with socialization and counseling, supervision of narcotics trafficking traffic both at the port and land which is the entry point for migrants in Pohuwato district. In addition, this supervision is also carried out routinely in places where transactions are usually held, for example nightclubs and locations where teenagers usually gather, and conduct operations or patrols or raids. Repressive efforts as the last step to take firm action against the perpetrator by imposing sanctions, as well as the implementation of rehabilitation involving various elements.